Steroidogenic pathways involved in androgen biosynthesis in eumenorrheic women and patients with polycystic ovary syndrome. Issue 158 (April 2016) - Saito, Kazuki; Matsuzaki, Toshiya; Iwasa, Takeshi; Miyado, Mami; Saito, Hidekazu; Hasegawa, Tomonobu; Homma, Keiko; Inoue, Eisuke; Miyashiro, Yoshimichi; Kubota, Toshiro; Irahara, Minoru; Ogata, Tsutomu; et al.
Graphical abstract: Highlights: Multiple steroidogenic pathways are involved in androgen production in women. Conventional pathways produce most androgens in polycystic ovary syndrome patients. Non-conventional pathways produce a weak androgen and potential precursors of DHT. Abstract: The conventional Δ5 and Δ4 steroidogenic pathways mediate androgen production in females. While multiple non-conventional pathways to dihydrotestosterone (DHT) have recently been postulated in humans, the functional significance of these pathways remains to be elucidated. The aim of this study was to clarify the origin of androgens in healthy women and in patients with polycystic ovary syndrome (PCOS), a multifactorial disorder characterized by androgen overproduction. We measured 13 steroids in blood samples of 31 eumenorrheic females and 28 PCOS patients using liquid chromatography-tandem mass spectrometry and chemiluminescent enzyme immunoassay. We found that 17-hydroxy (17-OH) progesterone (17-OHP), androstenedione (Δ4A), testosterone, androstanedione, androsterone, and androstanediol levels were higher in the patient group than in the eumenorrheic group, while levels of other steroids were comparable between the two groups. In the eumenorrheic group, DHT levels were correlated with testosterone, androstanedione, and androstanediol. Quantitative correlations were also observed among 17-OH allopregnanolone, androsterone, androstanediol, and DHT, and among Δ4A, androstanedione, androsterone, and androstanediol. In the patient group, DHT levels were correlated with testosterone levels, but not with androstanedione or androstanediol levels. Δ4A and testosterone paralleled 17-OHP. Androstanedione, androsterone, androstanediol, and 17-OH allopregnanolone were quantitatively correlated. In both groups, multivariable linear regression analyses suggested relationships between androsterone and androstanedione, as well as between androsterone and 17-OH allopregnanolone. These results indicate that multiple androgen biosynthesis pathways are operating in eumenorrheic females and PCOS patients. In PCOS patients, excessive androgens are produced primarily via the conventional pathways, while two alternative pathways; i.e., an androstanedione-mediated pathway and a so-called backdoor pathway, likely serve as sources of a weak androgen and potential precursors of DHT.